Analisis Gaya Bahasa Kiasan dalam Kumpulan Puisi Ketika Rakyat Pergi Karya Wiji Thukul - Azizah, Ririn Nurul; Marfina, Eka (CV. Eduartpia Publisher, 2023)
The study aims to find out the figurative language styles found in wiji thukul's collection of poems When people go. The method used in this study is qualitatively descriptive because the data is in the form of data descriptions. The type of research used in this study is library research. The data source used in this study is a collection of poems When the People Go by Wiji Thukul, and reinforced with other sources, such as books, journals, thesis, thesis, and articles that support research problems. The data collection techniques used in this study by reading, marking, recording, grouping, and analyzing. Data analysis techniques used in this research by collecting data, reducing data, presenting data, and attracting conclusions or verification. The results of this study showed that in wiji Thukul's collection of poems When People Went found 160 language style data including 9 simile language style data, 55 metaphorical language style data, 20 personification language style data, 8 depersonified language style data, 15 irony language style data, 13 sarcasm language style data, and 40 repetition language style data. It can be concluded that the most widely found style of language is the metaphorical language style. Keywords: Language Style, Figuratives, Works of Literature, Poetry